The role of parent-teacher association in the Philippine public schools - Garilao, Estela C. 1923- (University of the Philippines], 1955)
The proper role of the parent-teacher associations in the Philippine public school system is the subject of this study. Generally, the study investigated the role played by the parent-teacher associations in the Philippine Public school system.